Social Network Technologies as a Transformation Factor in Modern Vocational Education - Boris Skorodumov, Liliya Matronina, Olga Skorodumova, (Opción, 2019)
In this paper, the authors present the philosophical and methodological analysis of the influence of modern social networking technologies, based on collective strategies for existing and generated knowledge development, processing, structuring and storage, on new strategies formation in vocational education. The conducted research revealed that social network technologies development necessitates the search for new strategies in vocational education, as well as new education management methods introduction in the university cluster that is adequate to modern social conditions. In conclusion, a project-based approach to education has a significant heuristic potential.